Effectiveness of Motion Graphics and Visual Design Elements in Enhancing Brand Communication on Social Media Platforms - Mr. Rohit Dawar, Manoj Kumar Sharma, Dr. Aboli Niphadkar, Ajay Kumar (Journal of Daoist Studies, 2026)
Social media is growing at a fast pace and the way of communicating brands has changed drastically, therefore motion graphics and visual elements are vital for capturing consumers’ attention and increasing engagement. The study discusses the use of motion graphics and visual design elements to improve brand communication in social media, based on their impact on brand communication, consumer interaction and consumers' brand perception. The method of quantitative type was used and primary data were collected from 200 active social media users in Delhi NCR by the stratified random sampling technique by using a structured questionnaire. Descriptive statistics, correlation and regression analysis were used to analyze the collected data in MS Excel and SPSS 27. The study results show that motion graphics can substantially influence brand communication and brand perception among the consumers and visual design elements can substantially increase consumer engagement and interaction with the branded content. Overall, the findings suggest that incorporating dynamic visual elements into social media marketing strategies can help to build brand identity, enhance engagement, and boost communication effectiveness. The insights from the findings have implications for marketers, advertisers, designers and organizations wanting to improve their digital branding strategies and offer a basis for further studies on visual communication and social media marketing.